Are bank’s speculative profits at the expense of traders? A reply - S. SCHULMEISTER (PSL Quarterly Review, 2013)
The author states that empirical evidence suggests that two types of speculator currently exist in the foreign exchange markets: the first type of speculator simply follows trend movements in exchange rates; the second type anticipates the turning point in trends and thereby turns such runs around. The first type of trade is destabilising and the second type helps to maintain stability. However, both types depend upon an unstable system. Rational operators who attempt to determine fundamental equilibriums appear irrational in terms of the profits they earn. This constitutes a paradox for economic theorists.